2018
DOI: 10.1002/marc.201800679
|View full text |Cite
|
Sign up to set email alerts
|

Sn‐Polyester/Polyimide Hybrid Flexible Free‐Standing Film as a Tunable Dielectric Material

Abstract: Flexible films having high dielectric constants with low dielectric loss have promising application in the emerging area of high‐energy‐density materials. Here, for the first time, an organometallic, Sn‐polyester‐containing hybrid free‐standing film in polyimide matrix is reported. Polyimide, pBTDA‐HDA, is used with poly(dimethyltin glutarate) and poly(dimethyltin‐3,3‐dimethyglutarate) (pDMTDMG) for having a processable film with tunable dielectric properties. Hybrid film with 60% pDMTDMG and 40% PI (HB2) is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…By side-by-side comparing the dielectric properties of DPAES, BT/DPAES, and BT/c-DPAES, Dielectric materials that store electrical energy with static charge are ubiquitous in advanced electronic and electrical systems. [1][2][3] Compared with inorganic ceramic dielectrics, polymer dielectrics have higher breakdown strength and higher reliability, simultaneously possess the characteristics of scalable, lightweight, and easy-processing, which are the ideal of many power electronics, [4,5] power conditioning, [6] and artificial muscles for soft robotics. [7] However, polymer dielectrics are limited to relatively low operating temperatures and therefore cannot be used in extreme conditions, such as hybrid and electric vehicles, avionics and underground oil, and gas exploration.…”
mentioning
confidence: 99%
“…By side-by-side comparing the dielectric properties of DPAES, BT/DPAES, and BT/c-DPAES, Dielectric materials that store electrical energy with static charge are ubiquitous in advanced electronic and electrical systems. [1][2][3] Compared with inorganic ceramic dielectrics, polymer dielectrics have higher breakdown strength and higher reliability, simultaneously possess the characteristics of scalable, lightweight, and easy-processing, which are the ideal of many power electronics, [4,5] power conditioning, [6] and artificial muscles for soft robotics. [7] However, polymer dielectrics are limited to relatively low operating temperatures and therefore cannot be used in extreme conditions, such as hybrid and electric vehicles, avionics and underground oil, and gas exploration.…”
mentioning
confidence: 99%
“…5,15,21,22 Aer thorough structural and electrical experimentation and design, it has been found that the newly developed organometallic tin polyester systems exhibit high dielectric constants (6.1-6.8) and have excellent agreement with their computational predictions. 15,21,22 However, similar to BOPP, the thermal stability of Sn-polyesters still needs to be further improved as the ultra-fast charging-discharging process can produce a large amount of heat and increase the temperature of the energy storage device. 21,23 PI's are historically well-known for their high temperature resistance, chemical stability, and excellent mechanical and electrical performances.…”
Section: Introductionmentioning
confidence: 93%
“…15,21,22 However, similar to BOPP, the thermal stability of Sn-polyesters still needs to be further improved as the ultra-fast charging-discharging process can produce a large amount of heat and increase the temperature of the energy storage device. 21,23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BOPP displays high band gap (≈7 eV), high E b (>700 MV m −1 ), and extremely low tan δ (<0.02%). [ 46–48 ] The low tan δ ensures its excellent long‐term reliability, vital for power‐grid applications. [ 49 ]…”
Section: Dielectric Polymers For Film Capacitorsmentioning
confidence: 99%